Improved integrability and boundedness of solutions to some high-order variational problems - Voitovych, M.V. (Український математичний вісник, 2018)
We give a series of results on the improved integrability and boundedness of solutions to several high-order variational problems with strengthened coercivity. In particular, we consider the homogeneous Dirichlet problem on the minimum of integral functionals and study variational inequalities with unilateral and bilateral obstacles and with integral and gradient constraints.